Safe 3D Coverage Control for Multi-Agent Systems - Wenbin Liu; Kritapas Borikarnphanichphaisal; Jie Song; Olga Vasilieva; Mikhail Svinin (Actuators)
Multi-agent coverage control plays a crucial role in the modeling and coordination of complex systems, especially for teams of robots that, through frequent interactions with each other and their environment, can accomplish complex tasks in a distributed and parallel manner. However, most existing studies on coverage control for multi-agent systems are limited to two-dimensional environments, with few addressing the height factor critical to three-dimensional spaces. This study proposes a novel approach that adapts centroidal Voronoi tessellation (CVT) with a time-varying density function and Control Barrier Functions (CBFs) for dynamic coverage in 3D environments. By reconfiguring these methodologies, this approach enhances distribution and coordination efficiency within 3D spaces while ensuring safe, collision-free navigation. The simulation results validate the effectiveness of the proposed approach, demonstrating its potential for the efficient deployment of multi-robot systems, such as unmanned autonomous vehicles and unmanned autonomous underwater vehicles, in diverse operational contexts.